Using Artifacts as Triggers for Participatory Analysis - Mogensen, Preben Holst; Trigg, Randall H. (DAIMI Report Series, 1992)
Based on a study of a three-day workshop between users and developers, we show how artifacts like computer prototypes can be used to trigger productive discussions. We demonstrate how clashes between contextualized artifacts and the practitioners' (users) conceptions and experiences of their work practices trigger new understandings of current practice as well as possible futures. In this way, artifacts support the work of participatory analysis as well as participatory design.